Evaluation of the educational technology "Caring for dependent people" by family caregivers in changes and transfers of patients and tube feeding - Maria José Lumini Landeiro; Heloísa Helena Ciqueto Peres; Teresa Vieira Martins
ABSTRACT Objective: to assess the contributions of interactive educational technology "Caring for Dependent People" in the development of knowledge to family caregivers of dependent people in a household context and their satisfaction in its use. Method: quasi-experimental study, not randomized, of the before and after type, with a convenience sample of 65 family caregivers, from two Medicine services of a hospital in Porto, Portugal. The Control Group consisted of 33 family caregivers and the Experimental Group of 32, identified by consecutive sampling. The experimental group had access to educational technology at home. Data were collected by socio-demographic, satisfaction and evaluation of knowledge questionnaire, about how to feed by nasogastric tube, positioning and transferring the dependent person. The assessment in both groups had two moments: initial, during hospitalization and one month after discharge. Results: the experimental group had a larger increase in knowledge related to the use of the educational technology. In the control group the knowledge did not differ in the two evaluation time points. Conclusion: these results confirm the improvement of interactive educational technologies and in the training of family caregivers to care for dependents. This technology successfully met the technical quality and learning needs of caregivers, and was considered easy and stimulating.